The Relation Between Metacognitive Ability with Science Process Skills on Grade 8th Students in MTs Negeri 3 Parigi - Munir, Moch.; Kade , Amiruddin; Muslimin, Muslimin (Universitas Tadulako, 2019)
This study aims to determine the relations between metacognitive to science process skills on grade VIII students MTs Negeri 3 Parigi. This research is descriptive, the approach used is a quantitative approach, manifested in the form of numbers analyzed by statistics and the results are described. The population is students of MTs Negeri 3 Parigi Academic Year 2017-2018 with a population of three classes, with a sample of 30 students. The instrument used is a metacognitive questionnaire consisting of 50 questions and an essay about science process skills 6 questions test. The result of the prerequisite test of the research result is all metacognitive indicators of normal and linear distributed and based on the regression feasibility test show that all data is feasible for regression test. The result of the regression test and test of determination to obtain a value which is not significant. Based on the results of the research analysis it can be concluded that the relationship of each metacognitive indicator to science process skills was not significant even there were metacognitive indicators that reverse direction significantly. The magnitude of the relationship of each metacognitive indicator with science process skills maximum 15.3%.